Clinical outcomes and the probability of having one euploidy embryo using aCGH and NGS at different maternal age in PGT-A cycle. (April 2019) - Li, Chia-Jung; Lin, Chieh-Yu; Wang, Mei-Li; Hou, Chiung-Hui; Chang, Chia-Lin; Wu, Hsien-Ming; Yu, Hsing-Tse; Huang, Hong-Yuan; Wang, Hsin-Shih; Soong, Yung-Kuei
Abstract : Introduction: The impact of maternal age on euploidy rate and the outcome of PGT-Aisdemonstrated by many studies. But less understanding of the probability of finding at least one euploidy embryoaccordingto maternal age. In this study, weassess patients of different maternal age group in PGT-A cyclesusing aCGH and NGS: 1. Number of biopsy blastocyst per cycle; 2. Numbers of 2PN needed for aeuploidy embryo; 3. Euploidy rate; 4. The proportion of cycles having at least aeuploidy embryo; 5. Livebirth rate through frozen embryo transfer (FET). Materialand Methods: We retrospectively analyzed the PGT-A cycles enrolled from 2012 to 2016. To compare the clinical outcomes, the included data were separated into groups based on maternal age at IVF stimulation start. TE biopsy was performed on Day5 to 7 post-retrieval. All biopsied blastocysts were subjected to vitrification immediately. Biopsied TE cells were analyzed using array-CGH and NGS for all 23 chromosomes. Patients transferred euploidy embryo on progesterone Day6 in FET cycles. Results: The age groups for analysis were: < 35, 35–37, 38–40, 41–42, and >42. The cycles having biopsy were88.0%(22/25), 100%(18/18), 88.5%(23/26), 60%(9/15) and 82.3%(14/17). The number of biopsy blastocyst per cycle were 4.9(108/22), 5.8(105/18), 3.9(90/23), 3.2(29/9) and 1.6(23/14) and the number of 2PN needed for aeuploidy embryo were 6.8(218/32), 4.1(158/39), 7(189/27), 7.8(8/62) and 7.1(50/7). Euploidy rates were 29.6% (32/108), 37.1% (39/105), 30.0% (27/90), 27.6% (8/29), and 30.4% (7/23). The proportion of cycles having at least a euploidy embryo were 68.2%(15/22), 83.3%(15/18), 65.2%(15/23), 66.7%(6/9) and 35.7%(5/14). Pregnancy rate per FET were63.6%(7/11), 77.8%(7/9), 53.3%(8/15), 100%(1/1) and 50%(2/4). Live birth rates per FET were 63.6% (7/11), 77.8% (7/9), 46.7% (7/15), 100%(1/1) and 25% (1/4). Conclusions: In the course of PGT-A, the clinical outcomes and live birth rate can be predicted according to maternal age. Maternal age increase does not affect the number of 2PN needed for aeuploidy embryo, but it seems that women aged between 35 and 37are more likelyto benefit from PGT- A (the highestopportunity of having at least a euploidy embryo). The results of this research can assist doctors in patient consultations and help patients set realistic expectations.